The influence of international tourists' self-image congruity with a shopping place on their shopping experiences. (December 2019) - Han, Heesup; Moon, Hyoungeun; Kim, Wansoo
Abstract: To extend the existing knowledge about international tourists' shopping behaviors, this study examined the formation of their retention by considering the effect of self-image congruity, shopping value, emotional experiences, satisfaction, and ambient atmospherics of shopping places in tourist sites located in South Korea. A field survey was conducted. The collected data was analyzed using structural equation modeling and a test for metric invariance. Our empirical result showed that international tourists' self-image congruity with a shopping place significantly enhances its subsequent constructs. Shopping value, emotional experiences and satisfaction with shopping experiences were also significant contributors to increasing shopper retention toward the same shopping place, playing a significant mediating role. Moreover, ambient atmospherics had a significant moderating impact on forming shopper retention. Furthermore, shopper satisfaction included the greatest influence on retention. Overall, the proposed theoretical framework sufficiently accounted for retention.